Interactive effect between sleep and exercise on depressive symptoms in Chinese adolescents - Zou, Shoukang; Deng, Fang; Tan, Wenli; Fu, Yutong; Zhang, Hang; Xu, Hanmei; Tao, Yuanmei; Tang, Xian; Tang, Xiaowei; Xiong, Ping; Huang, Huiping; Huang, Ying; et al. (Frontiers in Psychiatry, 2023)
Objectives: To investigate the effects of sleep and exercise, individually and jointly, on depressive symptoms in Chinese adolescents.Methods: Cluster sampling was used to conduct a cross-sectional, electronic survey of 11,563 students from five primary and high schools in Sichuan Province in western China. The questionnaire contained custom-designed items to ask about sleep and exercise, while it used the Center for Epidemiologic Studies Depression Scale to assess depressive symptoms and the Core Self-Evaluations Scale to assess core self-evaluation. Data were analyzed using descriptive statistics and multivariate linear regression. Results: A total of 10,185 valid questionnaires were collected, corresponding to an effective response rate of 88.1%. Among the respondents in the final analysis, 5,555 (54.5%) were boys and 4,630 (45.5%) were girls, and average age was 15.20 ±1.72 years (range, 11-18 years). Just under half the respondents (4,914, 48.2%) reported insufficient sleep, while the remainder (5,271, 51.8%) had adequate sleep. Nearly one quarter (2,250, 22.1%) reported insufficient exercise, while the remainder (7,935, 77.9%) reported adequate exercise. Over half of respondents (5,681, 55.7%) were from vocational high schools, 3,368 (33.1%) were from junior high schools, 945 (9.3%) were from senior high school, and 191 (1.9%) were from primary school. The prevalence of depressive symptoms among all respondents was 29.5% (95% CI 28.7-30.4%). When other variables were controlled, depression score did not vary significantly with gender (B = -0.244, SE = 0.127, P = 0.054), but it decreased by 0.194 points per 1-year increase in age (B = -0.194, SE=0.037, P<0.001). Students getting adequate sleep had depression scores 2.614 points lower than those getting insufficient sleep (B = -2.614, SE = 0.577, P < 0.001), while students who engaged in adequate exercise had depression scores 1.779 points lower than those not exercising enough (B = -1.779, SE = 0.461, P < 0.001). Depression score decreased by 0.919 point per 1point increase in core self-evaluation score (B = -0.919, SE = 0.008, P < 0.001). In regression controlling for gender, age and core self-evaluation, sleep and exercise were found to interact significantly to influence depressive symptoms (B = 0.821, SE = 0.315, P = 0.009).